Maurice Dobb Political Economist - Shenk, Timothy. (Palgrave Studies in History of Economic Thought Series, 2013)
This book explores the life of the man whom even his critics acknowledged was one of the world's most significant Communist economists. From his outpost at the University of Cambridge, where he was a protégé of John Maynard Keynes and mentor to students, Dobb made himself into one of British communism's premier intellectuals.